Quitline Information Included on Cigarette Packaging: An Assessment of Country Adherence to WHO FCTC Guidelines, 2007 to 2018 - Christopher M. Seitz (MDPI AG, 2021)
The purpose of this study is to evaluate country adherence to the World Health Organization’s (WHO) Framework Convention on Tobacco Control (FCTC) guidelines in terms of including quitline information on cigarette packaging. Data were gathered from the WHO’s Global Health Observatory database. The study included countries that were signatories to the FCTC, had a toll-free quitline, and required health warnings on cigarette packaging. Countries were then classified by income level according to the World Bank. From 2007 to 2018, the number of countries that established a quitline increased from 34 to 60. During the same timeframe among those countries, the number of countries that included information about the quitline on cigarette packaging increased from 5 to 37, with a larger proportion (79%) of high-income countries promoting their quitlines on cigarette packaging compared to middle-income (45%) countries. Although there was an increase in adherence to the WHO FCTC guidelines, there is still a need for several countries to include quitline information on cigarette packaging.